Latihan Pliometrik dan Latihan Berbeban terhadap JumpingSmash Atlet Bulutangkis - Syahriadi Syahriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine whether there was an effect of plyometric training and weight training on the UKO Padang State University (UNP) Badminton Jumping Smash. This research method is a quasi-experimental method. The results of this study indicate that: 1) plyometric exercises have a significant influence on the leg muscle explosive power to support jumping smash of badminton athletes, 2) burdened training gives a substantial effect on leg muscle explosive ability to help to drop crash of badminton athletes, 3) plyometric exercises with exercise burden was carry out together. There is a significant effect on leg muscle explosive power to support the jumping smash of badminton athletes. Conclusion, burden training has a substantial impact on leg muscle explosive ability to support the badminton athlete's jumping smash Keywords: Plyometric and Load Training, Jumpingsmash